Estimativa da evaporação e eutrofização em reservatórios artificiais do semiárido: uma abordagem com modelagem em sensoriamento remoto - Praxedes, Carine Fernandes (2021)
Long periods of drought in arid and semi-arid regions often reduce the water level in reservoirs. This reduction is intensified by the high evaporation that tends to increase the concentration of nutrients in the waters of the reservoirs, favoring the eutrophication process. With this, the objective was to estimate evaporation using remote sensing data and calculate the balance of nutrients, Phosphorus (P) and Nitrogen (N), in reservoirs in the Brazilian semi-arid region. For this, the Pereira de Miranda, General Sampaio and Orós reservoirs were studied between 2015 and 2017. Evaporation was calculated using the SEBAL algorithm and satellite images, and the nutrient balance was determined through the inflow and outflow of nutrients. The coefficient of determination (R²) between the evaporation estimated by SEBAL and field methods was high for all reservoirs, mainly for the General Sampaio reservoir with a value equal to 0.96, followed by 0.89 for the Orós and 0.85 for the Pereira de Miranda. The Pereira de Miranda reservoir presented the best average evaporation estimate (4.98 mm day-1) in relation to the measured data, followed by General Sampaio (4.92 mm day-1) and Orós (6.26 mm Day 1). The mean absolute error (mm) was 0.26; 0.11; 0.22, respectively, for the Pereira de Miranda, General Sampaio and Orós reservoirs. Therefore, evaporation in water bodies in the Brazilian semiarid region can be quantified using satellite images. Regarding the nutrient balance, the flow and retention of total nitrogen (NT) and total phosphorus (PT) by the reservoirs was higher in the rainy season and the Pereira de Miranda reservoir accumulated 22.8 tons of NT and 2.8 tons of PT and General Sampaio accumulated 13 tons of NT and 1.5 tons of PT. Pereira de Miranda and General Sampaio reservoirs are retaining NT and PT nutrients, being considered storage sites in the hydrographic basin of the Curu River, resulting in the compromise of water quality by eutrophication and increasing costs to provide quality water for the different uses for which the reservoirs are intended.